2003
DOI: 10.1002/pd.735
|View full text |Cite
|
Sign up to set email alerts
|

Predicting complications of pregnancy with first‐trimester maternal serum free‐βhCG, PAPP‐A and inhibin‐A

Abstract: Low PAPP-A level is associated with the delivery of an SGA baby and high PAPP-A with the delivery of an LGA baby. High inhibin-A is associated with preterm delivery before 34 weeks. Feto-placental products in the first trimester do not prove to be useful as a screening tool for predicting pregnancy complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
88
3
8

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(109 citation statements)
references
References 41 publications
9
88
3
8
Order By: Relevance
“…Nevertheless, first-trimester PAPP-A MoM was not a useful predictor for development of GDM or earlyonset GDM. This is consistent with the results of three other studies 18,26,27 but contradicts others. 8,9,11,23,28,29 These published series are summarised in Table 5.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Nevertheless, first-trimester PAPP-A MoM was not a useful predictor for development of GDM or earlyonset GDM. This is consistent with the results of three other studies 18,26,27 but contradicts others. 8,9,11,23,28,29 These published series are summarised in Table 5.…”
Section: Discussionsupporting
confidence: 83%
“…8,9,11,23,28,29 These published series are summarised in Table 5. 8,9,11,18,23,[26][27][28][29] There are several possible explanations for the different results of these studies, including ours.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…Increased risk of low birth weight, intrauterine growth retardation and premature birth in women with low PAPP-A has been noted by others (Dugoff et al, 2004;Kabili et al, 2004;Krantz et al, 2004). In contrast, other studies have found an association between low PAPP-A and increased risk of low birth weight or intrauterine growth retardation, but not with preterm birth (Ong et al, 2000;Yaron et al, 2002a;Kwik and Morris, 2003;Tul et al, 2003). Furthermore, Morssink et al (1998) concluded that PAPP-A is not associated with either fetal growth restriction or preterm delivery.…”
Section: Low Papp-a and Adverse Outcomesmentioning
confidence: 72%
“…Several recent studies have shown an association between low first-trimester maternal serum pregnancy associated plasma protein-A (PAPP-A) levels and the subsequent development of pregnancy complications, including pre-eclampsia Smith et al, 2002;Yaron et al, 2002;Tul et al, 2003;Dugoff et al, 2004;Krantz et al, 2004;Spencer et al, 2005aSpencer et al, , 2006aSpencer et al, ,b, 2007aCowans and Spencer, 2007).…”
Section: Introductionmentioning
confidence: 99%